PENGEMBANGAN MEDIA PEMBELAJARAN CARD SORT BERBASIS MIND MAPPING KELAS IV SEKOLAH DASAR - Muflichatus Nur Fadilah; Arya Setya Nugroho; Iqnatia Alfiansyah (CV. ADIBA AISHA AMIRA, 2025)
The background to which this research was conducted was the lack of variety in the application of learning media at the elementary school level and students' lack of understanding of the broad range of social studies material. This research is a development research or Research and Development (R&D) using the 4D model but the researchers only reached 3 stages, namely Definition, Design and Development. The aim of this research is to develop Card Sort learning media based on Mind Mapping regarding material on types of work producing goods and services in elementary school social studies subjects. This research was tested on class IV students at UPT SD Negeri 84 Gresik as many as 16 students. The research results showed that the percentage of media validation results was 92.5% (very valid) and the percentage of material validation results was 93.75% (very valid) and the overall response percentage of class IV students at UPT SD Negeri 84 Gresik was 98.75% (Very Good). The conclusion of the results of this research shows that the development of Card Sort media based on Mind Mapping is feasible and effective in implementing fourth grade elementary school learning regarding types of work producing goods and services.